Comparable humoral and cellular immunity against Omicron variant BA.4/5 of once‐boosted BA.1/2 convalescents and twice‐boosted COVID‐19‐naïve individuals. Issue 2 (19th February 2023) - Kang, Chang Kyung; Kim, Min‐Gang; Park, Seong‐wook; Kim, Yong‐Woo; Lee, Chan Mi; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Nam Joong; Kim, Minji; Lee, Soojin; Kim, Ik Soo; Lee, Chang‐Han; et al.
Abstract: The fourth vaccination dose confers additional protective immunity against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in individuals with no prior coronavirus disease‐19 (COVID‐19). However, its immunological benefit against currently circulating BA.4/5 is unclear in individuals who have received a booster shot and been infected with Omicron variant BA.1/2. We analyzed immune responses in whom had been boosted once and did not have COVID‐19 ( n = 16), boosted once and had COVID‐19 when BA.1/2 was dominant in Korea (Hybrid‐6M group, n = 27), and boosted twice and did not have COVID‐19 (Vx4 group, n = 15). Antibody binding activities against RBDo BA.1 and RBDo BA.4/5, antigen‐specific memory CD4 + and CD8 + T‐cell responses against BA.4/5, and B‐cell responses against SARS‐CoV‐2 wild‐type did not differ statistically between the Hybrid‐6M and Vx4 groups. The humoral and cellular immune responses of the Hybrid‐6M group against BA.4/5 were comparable to those of the Vx4 group. Individuals who had been boosted and had an Omicron infection in early 2022 may not have high priority for an additional vaccination.